The Cymbidium goeringii genome provides insight into organ development and adaptive evolution in orchids - Ye Sun; Gui-Zhen Chen; Jie Huang; Ding-Kun Liu; Feng Xue; Xiu-Lan Chen; Shi-Qiang Chen; Chun-Gui Liu; Hong Liu; Hui Ma; Yuan Yuan; Diyang Zhang; et al. (Ornamental Plant Research, 2021)
Cymbidium goeringii is one of the important ornamental orchids, but its high-quality genome has not been previously published. Here, we report a chromosome-level genome of C. goeringii and report the gene family expansion, and contraction of the C. goeringii genome and the regulation mechanism of MADS-box genes in floral organ development. We constructed the pathways of carotenoids and anthocyanins that contribute to the different flower colors of C. goeringii and the metabolic pathways of the main components of flower fragrance. Moreover, we found the genes that regulate colourful leaves and analyzed the resistance genes involved in the adaptive evolution of C. goeringii. Our results provide valuable genomic resources for the improvement of orchids and other ornamental plants.